2014
DOI: 10.3892/ijo.2014.2743
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-483-3p and miR-21 is highly expressed in plasma of pancreatic cancer

Abstract: Several recent studies have revealed that microRNAs (miRNAs) have a role in carcinogenesis and cancer development, and that it is stably detectable in plasma/serum. The aim of this study was to test whether miR-483-3p as well as miR-21 could be plasma biomarkers for PDAC. The plasma samples were obtained from three groups including 32 pancreatic ductal adenocarcinoma (PDAC) patients, 12 patients with intraductal papillary mucinous neoplasm (IPMN) patients and 30 healthy controls (HC). We evaluated the plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
117
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(123 citation statements)
references
References 52 publications
(48 reference statements)
5
117
0
1
Order By: Relevance
“…Elevated expression of miR‐196a , miR‐183, and miR‐21 was found to predict poor survival of pancreatic cancer; miR‐196a and miR‐21 7 appear to be valuable in distinguishing normal pancreas from chronic pancreatitis and cancerous tissues; and miRNA‐21 , miR‐10a , and miR‐1246 mediate chemoresistance of multiple drugs and stemness in pancreatic cancer . Recently, miR‐483‐3p was observed to be significantly higher in the plasma of patients with pancreatic cancer and useful for discriminating pancreatic cancer from intraductal papillary mucinous neoplasm . In a previous study, a set of seven serum miRNAs ( miR‐20a , miR‐21 , miR‐24 , miR‐25 , miR‐99a , miR‐185 , and miR‐191 ) selected by qRT‐PCR effectively discerned pancreatic cancer cases at different disease stages from controls (healthy controls and patients with chronic pancreatitis) .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of miR‐196a , miR‐183, and miR‐21 was found to predict poor survival of pancreatic cancer; miR‐196a and miR‐21 7 appear to be valuable in distinguishing normal pancreas from chronic pancreatitis and cancerous tissues; and miRNA‐21 , miR‐10a , and miR‐1246 mediate chemoresistance of multiple drugs and stemness in pancreatic cancer . Recently, miR‐483‐3p was observed to be significantly higher in the plasma of patients with pancreatic cancer and useful for discriminating pancreatic cancer from intraductal papillary mucinous neoplasm . In a previous study, a set of seven serum miRNAs ( miR‐20a , miR‐21 , miR‐24 , miR‐25 , miR‐99a , miR‐185 , and miR‐191 ) selected by qRT‐PCR effectively discerned pancreatic cancer cases at different disease stages from controls (healthy controls and patients with chronic pancreatitis) .…”
Section: Discussionmentioning
confidence: 99%
“…Ng et al showed that miR-92 is significantly elevated in the plasma of CRC patients and might be a potential noninvasive molecular marker for CRC [12]. Accordingly, several subsequent studies have shown that miR-483 can serve as potential biomarkers for various cancers [1315], however the mechanism by which elevated miR-483 impacts the development of cancer remains unclear. The DLC-1 (Deleted in liver cancer 1) gene was originally discovered as a potential tumor suppressor frequently deleted in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Besides in tissues, recent evidence indicates the presence of miR-21 in various types of extracellular fluid, such as plasma [10, 11, 1533], serum [17, 29, 3450], CSF [5156], saliva [32, 57, 58], gastric juice [59], pancreatic juice [60], sputum [61], and pancreatic cyst fluid [62]. Although the diagnostic efficiency of extracellular miR-21 in cancers has been proposed by many researchers, the results are conflicting and inconclusive.…”
Section: Introductionmentioning
confidence: 99%